2019
DOI: 10.1007/s10714-019-2638-7
|View full text |Cite
|
Sign up to set email alerts
|

Translation in cylindrically symmetric vacuum

Abstract: Starting from the stationary cylindrically symmetric solution, but with the coordinates z and φ interchanged, and supposing that it could describe the vacuum spacetime of a translating cylinder, we investigate its physical and geometrical properties. This hypothesis is not entirely new since it has already been considered in a previous paper describing a translating source. We show that this metric is geometrically related to the vacuum field produced by a stationary rotating cylindrical source, known as Lewis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Notice that in the nonrigid rotation case where Ω = 0, (103) implies µ ′ = 0 and thus a priori nonstatic spacetimes, at variance with what obtains for a rigidly rotating fluid, see Section IV F 1. We have therefore implicitly defined a class of purely electric interior spacetimes sourced by a stationary nonrigidly rotating anisotropic fluid whose metric functions are solutions of the seven differential equations ( 10)-( 14), ( 98) and ( 101) and of the timelike condition (6). Notice that four among these equations can be replaced by ( 15)-( 17) and (103) which are partially integrated equations, i. e., interesting simplifications for future analytic or numerical resolutions.…”
Section: Purely Electric Spacetimesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notice that in the nonrigid rotation case where Ω = 0, (103) implies µ ′ = 0 and thus a priori nonstatic spacetimes, at variance with what obtains for a rigidly rotating fluid, see Section IV F 1. We have therefore implicitly defined a class of purely electric interior spacetimes sourced by a stationary nonrigidly rotating anisotropic fluid whose metric functions are solutions of the seven differential equations ( 10)-( 14), ( 98) and ( 101) and of the timelike condition (6). Notice that four among these equations can be replaced by ( 15)-( 17) and (103) which are partially integrated equations, i. e., interesting simplifications for future analytic or numerical resolutions.…”
Section: Purely Electric Spacetimesmentioning
confidence: 99%
“…The vacuum solution outside a cylindrical source in translation along its symmetry axis is mathematically akin to the Lewis solution with exchanged z and φ coordinates. It has been shown that they are however physically different [6]. Nonvacuum cylindrically symmetric spacetime investigations date back to 1937 when van Stockum gave the metric solution for a rigidly rotating infinitely long dust cylinder [7].…”
Section: Introductionmentioning
confidence: 99%
“…Back in 2014, Brito et al found the solution to the geodesic equations in Linet-Tian spacetime for few special cases [26]. Célérier et al explored radial, axial, and circular geodetic motions in a cylindrically symmetric translating spacetime, in 2019 [27]. In 2016, Hoseini et al came up with an analytic solution to the geodesic equation in a static cylindrically symmetric conformal spacetime [28].…”
Section: Introductionmentioning
confidence: 99%
“…A vacuum spacetime gravitationally sourced by a cylinder of matter in translating motion along its symmetry axis is mathematically similar to a Lewis solution where the coordinates z and φ have been exchanged. Their physical properties are however different [5].…”
Section: Introductionmentioning
confidence: 99%